2015
DOI: 10.1515/chempap-2015-0124
|View full text |Cite
|
Sign up to set email alerts
|

facile, highly efficient and novel method for synthesis of 5-substituted 1H-tetrazoles catalysed by copper(I) chloride

Abstract: The present study on tetrazole compounds, which have a wide area of application, proposes a new, simple and highly effective method. A series of 5-substituted 1H-tetrazoles were synthesised in DMF via the [3 + 2] cycloaddition reaction, in which different aryl nitriles with sodium azide were used and copper(I) chloride served as a catalyst. Short reaction times, high yields and simple procedures rendered this method attractive and useful for the organic synthesis of 5-substituted 1H-tetrazoles. A further advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Most of them are based on the addition of the nitrile group of the trimethylsilyl azide (TMSN 3 ) and the sodium azide (NaN 3 ). [16][17][18][19][20][21] Also, different new pathways have been improved, [22][23][24][25][26] such as the catalytic method using a stoichiometric amount of inorganic salts [27][28][29][30][31][32] and metal complex, 33 also using TMSN 3 and TBAF instead of metal salts under solvent-free conditions 17 or in micellar media 34 and ionic liquid. 35 However, these homogeneous catalysts pose difficulties in reusability, recovery and separation.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are based on the addition of the nitrile group of the trimethylsilyl azide (TMSN 3 ) and the sodium azide (NaN 3 ). [16][17][18][19][20][21] Also, different new pathways have been improved, [22][23][24][25][26] such as the catalytic method using a stoichiometric amount of inorganic salts [27][28][29][30][31][32] and metal complex, 33 also using TMSN 3 and TBAF instead of metal salts under solvent-free conditions 17 or in micellar media 34 and ionic liquid. 35 However, these homogeneous catalysts pose difficulties in reusability, recovery and separation.…”
Section: Introductionmentioning
confidence: 99%
“…During this reaction, silver azide is generated in‐situ and acts as a catalytic species. In another studies, Copper (I) chloride was used to get 5‐substituted‐1H‐tetrazole derivatives 47%–90% (Scheme 1; Esirden et al, 2015). In this study, researchers compared the effect of CuCl 2 with CuI, CuSO 4 , ZnCl 2 , AlCl 3 as catalyst and found that CuCl 2 were much effective and produced higher yield in short time.…”
Section: Conventional Approachmentioning
confidence: 99%
“…Although this procedure was simple enough, but using homogenous Zn (II) salts brought its own problem in separating of heavy metal at the end of the reaction, especially in industrial scale. In recent years, many homo‐ and heterogeneous catalysts have been used for this purpose such as silica sulfuric acid, Mw−Pd/Co@CNT NPs, Fe 3 O 4 @SiO 2 ‐TCT‐PVA−Cu(II), Pt‐NPs@VC, Zn hydroxyapatite, Zn/Al hydrotalcite, Cu 2 O, diisopropylethylammonium acetate, Fe(OAc) 2 , CdCl 2 , SiO 2 ‐H 3 BO 3 , Cu–MCM‐41, Pd‐SBT@MCM‐41, CuO nanoparticles, copper (I) chloride, [Cu(phen)(PPh 3 ) 2 ]NO 3 and so on . Although in many of these reported catalysts, the desired products were formed, but a number of them have some drawbacks such as prolonged reaction time, moderate yield, homogeneous or non‐scalable catalyst and problem in their reusability.…”
Section: Introductionmentioning
confidence: 99%